Tunable recurrent priming of lateral roots in Arabidopsis: more than just a clock? - Reyes Hernández, Blanca Jazmín; Maizel, Alexis (Current opinion in plant biology, 2023)
Lateral root (LR) formation in Arabidopsis is a continuous, repetitive, post-embryonic process regulated by a series of coordinated events and tuned by the environment. It shapes the root system, enabling plants to efficiently explore soil resources and adapt to changing environmental conditions. Although the auxin-regulated modules responsible for LR morphogenesis and emergence are well documented, less is known about the initial priming. Priming is characterised by recurring peaks of auxin signalling, which, once memorised, earmark cells to form the new LR. We review the recent experimental and modelling approaches to understand the molecular processes underlying the recurring LR formation. We argue that the intermittent priming of LR results from interweaving the pattern of auxin flow and root growth together with an oscillatory auxin-modulated transcriptional mechanism and illustrate its long-range sugar-mediated tuning by light.